1978
DOI: 10.1007/bf01538866
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic drug resistance in cystic fibrosis fibroblasts: Increased resistance to cyclic AMP

Abstract: In previous studies, cystic fibrosis (CF) fibroblasts were demonstrated to be resistant to the cytotoxic effects of ouabain, dexamethasone, and the sex hormones, dihydrotestosterone, 17beta-estradiol, and progesterone. We now show that CF fibroblasts also exhibit greatly increased resistance to the cytotoxic effects of exogenous dibutyryl cyclic AMP (cAMP), as well as to isoproterenol and theophylline, drugs which are known to increase endogenous levels of cAMP. CF cells were also shown to have normal amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1979
1979
1991
1991

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…This selective effect of dexamethasone has been proposed as the basis of a diagnostic test for the disease in fetuses and in individuals heterozygous for the trait (2). Our results do not agree with the findings reported in (1)(2)(3)(4). Our results do not agree with the findings reported in (1)(2)(3)(4).…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…This selective effect of dexamethasone has been proposed as the basis of a diagnostic test for the disease in fetuses and in individuals heterozygous for the trait (2). Our results do not agree with the findings reported in (1)(2)(3)(4). Our results do not agree with the findings reported in (1)(2)(3)(4).…”
contrasting
confidence: 99%
“…Their procedure (1)(2)(3)(4)12) has been to add enough cells to each experimental dish to produce 75 to 100 colonies. Their procedure (1)(2)(3)(4)12) has been to add enough cells to each experimental dish to produce 75 to 100 colonies.…”
Section: Concenmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, no other laboratory has published an attempt to replicate these findings (64). The phenomenon is not explained by differences in protein kinase activity, phosphodiesterase activity, CAMP binding sites, steroid binding sites, or Na/K ATPase activity, or its inhibition by ouabain (22).…”
Section: Fibroblastsmentioning
confidence: 86%
“…Epstein and Breslow have reported that CF fibroblasts are more resistant to the toxic effects of dexamethasone (21), ouabain (in potassium-free medium) (20), sex steroids (S), dibutyryl cyclic AMP, isoproterenol and theophylline than normal cells (22); fibroblasts from obligate heterozygotes for CF are intermediate (6). One cell line obtained from the amniotic fluid of a mother who previously had a child with CF and later fibroblasts from the skin of the aborted fetus showed increased resistance similar to homozygotes (6).…”
Section: Fibroblastsmentioning
confidence: 99%